Assessing the Impact of Service Quality on Consumers Satisfaction: A Comparative Study of Commercial vs Islamic Banks in Pakistan - Muhammad Waqas Yousuf; Farhan Ahmed; Suman Talreja (Ekonomi Syariah IAIN Kudus, 2018)
This study aims to show the path that Islamic banking follows of Sharia’ h while on the other hand commercial banks obeys commercial regulations and rules for the purpose of banking. The main objective of the Islamic banking is to offer interest free services and products which obeys the path of Sharia’ h and Islamic banking system makes transaction on the foundation of profit and loss, while on the other hand commercial banks are business oriented banks. The sampling method used in this research was convenience sampling with a sample size of 200 which were the customers of the banks and the research design of the questionnaire used was exploratory The questionnaire was distributed in 4 banks 2 commercial and 2 Islamic banks respectively. Dependent variables are ‘customer expectation and perception’ while on the other hand independent variable that are used this research are ‘reliability, assurance, tangibles, empathy and responsiveness. The results which are derived from this research shows a negative or less impact of two service quality dimensions on both banks which are Assurance and Empathy. The highest perceived service dimension is “Reliability,” that refers to the reliability of their products and promise to provide the best service quality to their customers. While the lowest perceived service was observed towards “Empathy,” the other two dimension with highest value are tangibility and responsiveness which means that customers’ of both commercial and Islamic banks like tangible service and the quick responsiveness towards providing them the best service.